Hydrological behaviour of a small catchment in the dehesa landuse system (Extremadura, SW Spain) - Ceballos, Antonio; Schnabel, Susanne (Journal of Hydrology, 1998)
Investigations of the hydrological processes operating in a small experimental catchment representative of the dehesa ecosystem were carried out. The dehesa constitutes a system of agro-silvo-pastoral landuse, which is characterized by a Mediterranean, semi-arid climate. The study includes an analysis of the relationships between rainfall, soil water content and discharge, as well as the establishment of the annual water budget. The results demonstrate a complex hydrological response. The relationships between the factors involved and the operating processes are difﬁcult to explain because of the decisive role played by the valley bottoms. These areas typically possess a sediment ﬁll, and contrast with the shallow soils developed on the hillslopes. Genesis and quantity of runoff (Hortonian or saturation) measured at the outlet depend on the antecedent moisture conditions of the valley bottoms because of their water-retention capacity. Annual runoff coefﬁcients are similar to those reported from other semi-arid areas. The analysis of the annual water budget shows that rainfall is positively related with both actual evapotranspiration and discharge
The following values have no corresponding Zotero field: publisher: Elsevier
Keywords: Dehesa; Runoff–rainfall relationship; Semi-arid areas; Small catchment; Water budget

Hydrological behaviour of a small catchment in the dehesa landuse system (Extremadura, SW Spain) - Ceballos, Antonio; Schnabel, Susanne (Journal of Hydrology, 1998)
Investigations of the hydrological processes operating in a small experimental catchment representative of the dehesa ecosystem were carried out. The dehesa constitutes a system of agro-silvo-pastoral landuse, which is characterized by a Mediterranean, semi-arid climate. The study includes an analysis of the relationships between rainfall, soil water content and discharge, as well as the establishment of the annual water budget. The results demonstrate a complex hydrological response. The relationships between the factors involved and the operating processes are difﬁcult to explain because of the decisive role played by the valley bottoms. These areas typically possess a sediment ﬁll, and contrast with the shallow soils developed on the hillslopes. Genesis and quantity of runoff (Hortonian or saturation) measured at the outlet depend on the antecedent moisture conditions of the valley bottoms because of their water-retention capacity. Annual runoff coefﬁcients are similar to those reported from other semi-arid areas. The analysis of the annual water budget shows that rainfall is positively related with both actual evapotranspiration and discharge
Keywords: Dehesa; Runoff–rainfall relationship; Semi-arid areas; Small catchment; Water budget

COMPARISON OF THE HYDROLOGICAL CHARACTERISTICS OF 3 SMALL EXPERIMENTAL HOLM OAK FORESTED CATCHMENTS IN NE SPAIN IN RELATION TO LARGER AREAS - Piñol, J; Avila, a; Escarre, A; LLEDO, M J; Rodà, F (VEGETATIO, 1992)
Precipitation and streamflow have been measured in three small (0.04-0.52 km2) experimental catchments covered by dense holm oak (Quercus ilex L.) forests. Two of them are in the Prades mountains and one in the Montseny mountains (NE Spain). Here we test the hydrological representativeness of these catchments against the streamflow record at two nearby larger (34-60 km2) catchments, one from each massif. Comparisons of (i) annual streamflow, (ii) seasonal distribution of streamflow, and (iii) flow duration curves were made. At Prades, for the period of common record, mean annual precipitation was about 580 mm, and mean annual streamflow 44-81 mm at the two experimental catchments and 102 mm at the larger one. Most streamflow occurred during winter and spring in the three catchments. At Montseny, rainfall was higher, and mean annual streamflow was 495 mm in the experimental catchment, and 760 mm in the larger catchment, though these data were obtained in different periods in each catchment. Streamflow was roughly equal in autumn, winter and spring. At both sites flow duration curves were fairly similar in the small experimental catchments and the larger catchments. The higher streamflow at Montseny is reflected in its flow duration curves being well above those at Prades. The experimental catchments at Prades are thus fairly representative of the investigated hydrological characteristics. At Montseny, hydrological differences between the experimental catchment and the larger catchment are probably due to the higher mean altitude of the latter and to the non-overlapping periods of their streamflow records.
Keywords: EXPERIMENTAL CATCHMENT; montseny; prades; QUERCUS-ILEX; STREAMFLOW; Water budget